Prótesis Valvular Cardíaca. Vigencia del Diseño con Oclusor Esférico en una Jaula Metálica - Espino Vela, J.; Reyes Rodríguez, S.; Saenz Arroyo, L. (Revista Mexicana de Ingenieria Biomedica, 1998)
Cardiovascular surgeons disagree on the performance of different heart valve prostheses. The best opinions are based on statistical analysis of results of outcome and performance studies, as opposed to others based on prejudice or bias based on the design, trademark, or other marketing efforts with little or no scientific content. A frequent argument is that a design is too old, and that newer designs are better. This article is a review of the literature on the subject to understand the best scientific opinions. The Ball Valve first appeared in 1961 and gained worldwide acceptance for 20 years. Eventually the low-profile valve designed appeared, with an oscillating disc, which temporarily gained the surgeon’s preference. The Ball Valve regained acceptance when the Food and Drug Administration excluded the low-profile design from the market in the U.S. Today, the double valve is generally preferred, but some surgeons still prefer the Ball Valve for mitral or tricuspid replacements with several valid reasons; the ball valve is more resistant, has no cardiac energy loss due to reflux, and patients suffer fewer thromboembolic episodes, and of lesser severity than with other valves. In addition, all patients with any of the heart valve designs is forced to use anticoagulants indefinitely.